Application of The Business Judgment Rule in Decision-Making by The Board of Directors of State-Owned Enterprises - Firli Syarifah; Wahyudi Wahyudi (Journal of Progressive Law and Legal Studies, 2026)
State-Owned Enterprises (SOEs) play a strategic role in Indonesia’s national economy by combining business objectives with public service mandates. This dual function places SOE directors in a difficult position when making business decisions involving risks, as any financial loss may lead to legal or even criminal liability. The Business Judgment Rule (BJR) serves as a legal principle that protects directors who make business decisions in good faith, with due care, and without conflicts of interest. In Indonesia, this principle is reflected in Article 97 paragraph (5) of the Company Law and the SOE Law, and further supported by Supreme Court Regulation No. 4 of 2023. This study employs a normative juridical method with a descriptive-analytical approach to statutory regulations and legal doctrines. The findings indicate that although BJR has a legal foundation, its practical application remains problematic due to overlapping regulations, differing perspectives between business actors and law enforcement authorities, and limited understanding of the requirements for BJR protection. Therefore, clearer legal standards and consistent law enforcement are necessary to ensure that BJR functions effectively as both a protective and accountability mechanism for SOE directors.